Estimates of glomerular filtration rate based on creatinine and cystatin c equations in critically ill patients - Mohd Hanafiah, Farah Nadia; Md Ralib, Azrina; Abd Hadi Mohamed, Rozilah; Ramly, Nur Fariza; Abd Rahim, Mohd Shahrir (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2021)
Introduction and Aim: Accurate assessment of renal function in the critically ill is a complex task. Estimated glomerular filtration rate (eGFR) is the best indicator to help physicians estimate kidney function and determine different stages of kidney disease. eGFR can be calculated using serum Creatinine (SCr), or serum Cystatin C (SCysC), age, body size, race and gender using different equations. We evaluated eGFR based on SCr and SCysC equations in critically ill patients to find an accurate, precise, and less biased equation for GFR estimation.